A High-Resolution Terahertz Electric Field Sensor Using a Corrugated Liquid Crystal Waveguide - Lan-Lan Xu; Yi Gong; Ya-Xian Fan; Zhi-Yong Tao (Crystals, 2019)
Liquid crystals (LCs) can always reflect variable optical properties in a broad terahertz (THz) band under external electric or magnetic fields. Based on the measurements of these varying properties, we can realize electric and magnetic field sensing with very high sensitivity. Here, we theoretically and numerically demonstrate a type of electric field sensor in the THz frequency range based on the defect mode arising in a periodically corrugated waveguide with liquid crystals. The Bragg defect structure consisting of periodically corrugated metallic walls and a defect in the middle can provide a narrow transmitted peak with controllable bandwidth, which can be used for external field sensing when it is filled with LCs. The molecular orientation of nematic LCs (E7) is not only very sensitive to the applied DC electric field but also very crucial to the effective refractive index of E7. Changing the effective index can efficiently shift the frequency of the transmitted peak in the THz spectrum. The simulated results show that the sensitivity can reach as high as 9.164 MHz/(V/m) and the smallest resolution is 0.1115 V/m. The proposed sensor and its significant performance could benefit electric field sensing and extend the applications of THz technology.